The Financial Performance of Islamic REITs in Malaysia - Siti Marsila Mhd Ruslan (Asian Academy of Management Journal of Accounting and Finance, 2019)
Islamic real estate investment trusts (iREITs) is a fund or a trust that owns and manages income producing commercial real-estate which complied with Shariah. The aim of the paper is to study the recent performance of four iREITs in Malaysia, namely Al-‘Aqar Healthcare REIT, Axis REIT, Al-Sal?m REIT and KLCC REIT, from 2012 until 2016. Trend analysis is adopted to analyse the performance focusing on dividend distribution per unit (DPU) and net asset value (NAV). Based on the findings, both DPU and NAV performance show a good track record and this is evident in the case of Al-‘Aqar Healthcare REIT, KLCC REIT and Al-Sal?m REIT. Generally, it can be concluded that iREITs provide an attractive investment tool as it generates steady income in the form of dividend to the shareholders, while at the same time backed by quality underlying assets.